2022
DOI: 10.32598/jgums.30.4.1786.1
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Uric Acid Level and Glycemic Status in Type 2 Diabetic Patients in Rasht

Abstract: Background: Diabetes is one of the most common and costly chronic diseases with an increasing prevalence in all around the world. On the other hand, the relationship between Uric Acid (UA) level and glycemic index in type 2 diabetic patients is not clear. Objective: The aim of this study is to evaluate the UA level and glycemic status of type 2 diabetic patients. Methods: A total of 230 patients with type 2 diabetes were studied in this cross-sectional study, who referred to Razi and Besat clinics in 2020. Res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…In this regard, studies indicated that BMI, waist circumference (WC), and waist-to-hip ratio (WHR) anthropometric index are comparable in predicting diabetes onset and following complications [ 9 , 10 ]. Moreover, patients with diabetes usually illustrated abnormalities in their laboratory findings [ 11 , 12 ]. The WHR associated with fasting blood sugar (FBS) levels, proteomic profile, and lipid profiles reflect its role in assessing metabolic health.…”
Section: Introductionmentioning
confidence: 99%
“…In this regard, studies indicated that BMI, waist circumference (WC), and waist-to-hip ratio (WHR) anthropometric index are comparable in predicting diabetes onset and following complications [ 9 , 10 ]. Moreover, patients with diabetes usually illustrated abnormalities in their laboratory findings [ 11 , 12 ]. The WHR associated with fasting blood sugar (FBS) levels, proteomic profile, and lipid profiles reflect its role in assessing metabolic health.…”
Section: Introductionmentioning
confidence: 99%
“…High serum UA (SUA) levels, and hyperuricemia, are associated with gout, hypertension, kidney stones, kidney disease, cardiovascular complication, and metabolic syndrome [ 3 ]. Some diseases, such as metabolic syndrome and type 2 diabetes mellitus (T2DM), are often considered lifestyle-related diseases due to their pathological basis [ 4 – 6 ]. Diabetes has become an epidemic over the past few decades as one of the most significant global health emergencies of the 21st century.…”
Section: Introductionmentioning
confidence: 99%